Unveiling the Knowledge Landscape of Islamic Finance for Poverty Alleviation: Evidence from Bibliometric Analysis - Azwar Azwar; Abur Hamdi Usman (International Journal of Kita Kreatif, 2026)
This study aims to comprehensively map the knowledge landscape of Islamic finance in relation to poverty alleviation using a descriptive-quantitative bibliometric approach. The analysis is based on secondary data from the Scopus database, covering publications from 2000 to 2025. The findings indicate a consistent and significant growth in publications, reflecting increasing scholarly attention and the rising relevance of Islamic finance as a strategic instrument for poverty reduction. The intellectual structure of the field is shaped by key contributors such as Bhuiyan, A.B. and Hassan, M.K., alongside highly cited studies focusing on Islamic microfinance and social finance models. Major publication outlets, including the International Journal of Ethics and Systems and the Journal of Islamic Accounting and Business Research, play a central role in disseminating research, while institutions from Malaysia—particularly the International Islamic University Malaysia—dominate the landscape. At the country level, Malaysia and Indonesia emerge as leading contributors, highlighting the prominence of Southeast Asia. Thematic analysis reveals a strong concentration on core topics such as poverty alleviation, development, Islamic microfinance, and zakat, indicating a shift toward more applied and evidence-based research. Overlay visualization shows a transition from early technical and operational studies to more recent work emphasizing sustainability, policy, and governance, especially within the framework of the Sustainable Development Goals (SDGs). However, density analysis suggests that emerging areas such as Islamic fintech, accessibility, and global institutional perspectives remain underexplored. The field is undergoing consolidation and gradual transformation. While its core structure is well established, gaps remain in integrating Islamic commercial and social finance and in advancing technology-driven research, offering significant opportunities for future studies.